2016
DOI: 10.1038/nm.4051
|View full text |Cite
|
Sign up to set email alerts
|

Prospective identification of neoantigen-specific lymphocytes in the peripheral blood of melanoma patients

Abstract: Detection of lymphocytes that target tumor-specific mutant neoantigens--derived from products encoded by mutated genes in the tumor--is mostly limited to tumor-resident lymphocytes, but whether these lymphocytes often occur in the circulation is unclear. We recently reported that intratumoral expression of the programmed cell death 1 (PD-1) receptor can guide the identification of the patient-specific repertoire of tumor-reactive CD8(+) lymphocytes that reside in the tumor. In view of these findings, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
612
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 749 publications
(649 citation statements)
references
References 41 publications
34
612
1
2
Order By: Relevance
“…7 Furthermore, Gros and colleagues were able to recently identify PD1 + CD8 + T cells in circulation of three melanoma patients that targeted unique patient-specific neoantigens. 31 Our findings, that tumor antigen specific T-cells (including EGFR, MAGE and HPV) in the periphery express PD-1 and CTLA-4, support these observations. Thus, circulating TA-specific T cells can be identified in peripheral blood with important consequences for the development of individualized TCR analyses and therefore personalized therapies.…”
Section: Discussionsupporting
confidence: 82%
“…7 Furthermore, Gros and colleagues were able to recently identify PD1 + CD8 + T cells in circulation of three melanoma patients that targeted unique patient-specific neoantigens. 31 Our findings, that tumor antigen specific T-cells (including EGFR, MAGE and HPV) in the periphery express PD-1 and CTLA-4, support these observations. Thus, circulating TA-specific T cells can be identified in peripheral blood with important consequences for the development of individualized TCR analyses and therefore personalized therapies.…”
Section: Discussionsupporting
confidence: 82%
“…34 Moreover, expression of checkpoint molecules such as PD1 on circulating CD8 + T-cells is a biomarker of tumor antigen specificity. 35 We therefore dichotomized the HPV+ HNSCC data set based on median LAG3, PD1, TIGIT, or TIM3 expression and calculated the impact of high versus low expression on overall patient survival (Figure 7, black and red curves). Higher than median expression of any of these genes predicted markedly improved survival in HPV+ HNSCC over those patients with tumors expressing these markers at levels below the median.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, Simon et al have recently showed that PD-1 expression identifies Ag-specific T-cell clones with high avidity, 28 and Gros et al described PD-1 + neoantigen-specific anti-tumor CD8 + T cells, either circulating or intratumoral. 56 …”
Section: Discussionmentioning
confidence: 99%